Multicultural Awareness and Practices among Malaysian Primary School Teachers - Yusuf, Qismullah; Marimuthu, Sangeetha; Yusuf, Yunisrina Qismullah (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
This study was designed and aimed at identifying the awareness and practices of multicultural awareness among primary school teachers in Malaysia. It attempts to identify their awareness of multicultural concept when dealing with their students and staffs at their school. This awareness was measured by three variables: awareness, knowledge and skills. A number of 41 questions which inquired about the three variables were distributed randomly to 50 primary school teachers in Malaysia. These teachers were from three ethic types of primary schools: Tamil, Chinese and Malay primary schools. The reason for choosing the three different mainstream schools was because they represented the main different multicultural practices in the country. From these participants, five teachers were selected for further interviews to obtain richer data. The findings revealed that the awareness of multicultural education among primary school teachers was still at the medium level. Thus, this study suggests that there should be a multicultural awareness campaign at all schools in Malaysia in order to ensure that each student, no matter from what backgrounds they are from, feel they are part of the Malaysian society as a whole. The study also found that the awareness should start from the home, environment and peer and through parental guidance because school is a bridge between home and the society that will form one Malaysian society to achieve vision 2020.